Design of current differential protection system for distribution network based on 5G wireless communication - FENG Xinglong; KONG Fengfeng; HUO Kailong; ZHOU Guohua; ZHAO Fang (Diance yu yibiao)
In order to quickly realize the current protection of distribution network and avoid maloperation or refusal of operation, a current differential protection system for distribution network based on 5G wireless communication is designed. With the development of 5G communication technology, its characteristics of high reliability and ultra-low delay make it an ideal communication mode for differential protection of distribution network. By constructing slicings of 5G network, the average end-to-end delay of 5G can reach less than 10 ms, which can effectively meet the differential protection requirements of distribution network. The data acquisition module collects the phase current and zero-sequence current information on both sides of the distribution network through the current transformer, and transmits the collected information to the differential protection module. According to the differential protection action criterion calculated by digital signal processing (DSP) controller, the differential protection of distribution network current and related automation functions are completed. The timing module receives Beidou/GPS satellite timing to assist the synchronous sampling of the differential protection modules on both sides of the substation and the switching post. 5G central processing element (CPE) communication module uses 5G wireless communication network to realize data transmission and transmission through the centralized cross domain mapping network architecture in the network slice. Under the condition of regional fault in the distribution network, the differential protection logic in the two differential protection modules act respectively to protect the action outlet to complete the current differential protection of the distribution network. The experimental results show that all the test results of the system in this paper reach the expected test objectives, and the system in this paper still completes the action accurately at a fast speed under the condition of high transition resistance value.